Congenital ectropion uveae (CEU) with refractory glaucoma: Early trabeculectomy saves vision. Issue 2 (March 2021) - Singh, Kirti; Bhattacharyya, Mainak; Gotmare, Nikhil; Joon, Annu; Aggarwal, Himshikha; Singh, Arshi
We report the case of congenital ectropion uveae in a 10-year-old boy with intractable unilateral glaucoma but no systemic association. Glaucoma in congenital ectropion uveae is often poorly responsive to medial therapy and requires surgical intervention. Satisfactory results are possible if diagnosis is established early and timely surgery performed, as was the case in our patient.